THE EFFECT OF INQUIRY-BASED LEARNING ON LEARNING THE FOREHAND JUMP SKILL ON THE GYMNASTICS PLATFORM ACCORDING TO DUAL CODING - L. Lukman Saleh Karim (Proximus Journal Publishing, 2025)
This research aims to study the effect of inquiry-based learning on improving the forehand jump skill using the gymnastics platform. It also seeks to understand the impact of this type of learning on third-year students in the Department of Physical Education and Sports Sciences according to the dual coding system. The experimental approach was , adopted by preparing two experimental and control groups using a factorial method (2 x 3). Thirty-six students participated in the study, deliberately selected from a total of 42 students in the College of Education - Department of Physical Education and Sports Sciences at Al-Kitab University during the 2023/2024 academic year, during the second semester. Participants were divided into six groups based on the dual coding system. After preparing the skill test along with instructional exercises for this experimental method, pre-tests were conducted on Saturday, March 2, 2024, and concluded on Wednesday, March 20, 2024. The study included the implementation of four skill learning units over two consecutive weeks. Data was collec ted and then statistically processed using SPSS. The study concluded that inquiry-based learning vocabulary can be used in third-grade physical education and sports science lessons. Students who received this method demonstrated a greater ability to learn the front handspring skill compared to the traditional method. This method was found to be most suitable for students with dual coding, followed by students with pictorial coding, and then students with verbal coding. The study emphasizes the importance of focusing on practical applications and increasing the proportion of inquiry activities within artistic gymnastics education units to enable students to practice performance and discover knowledge effectively
Keywords: inquiry-based learning; front handspring